Implementation of Integral Character Education Based on School Curriculum Integration - Supriyadi; Febriyanti, Berliana Khofifah; Tirtoni, Feri (MIMBAR PGSD Undiksha, 2024)
The implementation of character education in educational units is oriented towards developing an educational culture based on main character values in an integral manner. However, some graduates do not yet appear to be integral individuals. This phenomenon requires integration of character education content in the curriculum. The aim of this research is to analyze the strengthening of students' integral character education and the implementation of integral character education in the implementation of integrated school and madrasa curriculum. The approach used is qualitative research with a case study type in Islamic Elementary Schools. The data collection methods used in the research used interviews, observation and documentation. Data analysis method consist of data collection, condensation, data presentation, and conclusions. The research results found that integral character education was strengthened through a habituation approach, namely (1) praying before learning begins; (2) singing the Indonesian Raya song every day after reading prayers together; (3) reading Asma al-Husna after praying and singing the song Indonesia Raya; (4) provide ice breaking before learning begins and motivate learning every day before starting learning; (5) literacy activities are carried out 15 minutes before learning; (6) Dhuha prayer and Dhuhur prayer in congregation; (7) memorization of the Qur'an in surah in juz 30 which is done every day; (8) morning alms, and (9) reading surah al-Kahf every Friday for high school students.